2013
DOI: 10.1159/000346585
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling and Identification of Plasma Proteins of Spinocerebellar Ataxia Type 2 Patients

Abstract: Background: Spinocerebellar ataxia type 2 (SCA2) is an autosomal-dominant hereditary ataxia characterized by progressive gait and limb ataxia, dysarthria, slow saccades, neuropathy and dementia. The expansion of trinucleotide CAG repeats in the coding region of the ATXN-2 gene leads to expanded polyglutamine stretch in the mutated protein which causes neuronal death. Objective: In this study, we investigated the blood plasma of SCA2 patients to find protein biomarkers. Methods: Thirty-two ataxia patients clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…3A,B). Earlier reports on dysregulated lipid metabolism in a number of neurodegenerative diseases, including Alzheimer's, Parkinson's, Niemann-Pick's, and Huntington's diseases (Adibhatla and Hatcher, 2008); spinocerebellar ataxia type 12 (Swarup et al, 2012); and spinocerebellar ataxia type 2 (Swarup et al, 2013), support the present observations found in FRDA. Low levels of apoC-II and C-III obtained in plasma of FRDA patients in our study indicate their possible role in altered lipid metabolism among FRDA patients.…”
Section: Downregulated Proteinssupporting
confidence: 91%
“…3A,B). Earlier reports on dysregulated lipid metabolism in a number of neurodegenerative diseases, including Alzheimer's, Parkinson's, Niemann-Pick's, and Huntington's diseases (Adibhatla and Hatcher, 2008); spinocerebellar ataxia type 12 (Swarup et al, 2012); and spinocerebellar ataxia type 2 (Swarup et al, 2013), support the present observations found in FRDA. Low levels of apoC-II and C-III obtained in plasma of FRDA patients in our study indicate their possible role in altered lipid metabolism among FRDA patients.…”
Section: Downregulated Proteinssupporting
confidence: 91%
“…A recent proteomic study on SCA2 patient blood plasma showed a large increase in the apolipoprotein E (ApoE) protein level (Swarup et al, 2013). In addition to being involved in lipid and cholesterol transport and metabolism, ApoE has previously been shown to be protective against oxidative damage by ROS such as H2O2, which we see increased in our SCA2 patient cells (Miyata & Smith, 1996;Tangirala et al, 2001).…”
Section: Transcriptional Regulation Of Proteins Involved In Oxidativesupporting
confidence: 47%
“…SCA2 has been suggested to be linked to oxidative stress, yet the source of oxidative stress in patients is not well characterized (Almaguer-Gotay et al, 2014;Swarup et al, 2013). In this study we investigated the level of mitochondrial oxidative stress by assessing superoxide levels in fibroblasts from SCA2 patients and controls.…”
Section: Mitochondrial Oxidative Stress and Antioxidant Response In Pmentioning
confidence: 99%
See 2 more Smart Citations